2022
DOI: 10.1057/s41291-022-00208-z
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel relational influences on HRM practices: a cross-country comparative reflective review of HRM practices in Asia

Abstract: In this paper, we respond to the calls for context-specific scholarship and research on human resource management (HRM) in Asia. We provide an overview of and key insights into HRM in five Asian countries, representing five key regions: China (East Asia), India (South Asia), Kazakhstan (Central Asia), United Arab Emirates (West Asia), and Vietnam (Southeast Asia). Based on our comprehensive, pan-Asian review, we develop a reflective, comparative, and relational understanding of HRM practices. In doing so, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…Hence, this anomaly should be corrected. Further, the authors (Malik et al, 2022) in their research found that in China, four kinds of HRM practices exist, that is, commitment, collaboration, control and contract-based HRM systems. It was found that a combination of the first two systems led to higher innovation in the firms and a combination of the first three led to better cost constraints.…”
Section: Human Resource Management Practices Of Chinamentioning
confidence: 99%
“…Hence, this anomaly should be corrected. Further, the authors (Malik et al, 2022) in their research found that in China, four kinds of HRM practices exist, that is, commitment, collaboration, control and contract-based HRM systems. It was found that a combination of the first two systems led to higher innovation in the firms and a combination of the first three led to better cost constraints.…”
Section: Human Resource Management Practices Of Chinamentioning
confidence: 99%
“…Correspondingly, human resource management and talent management have become key in Asia (Froese et al, 2020;Li et al, 2022). Human resource management in Asia has been influenced by the West and partially developed their own styles (Malik et al, 2022). More empirical research is encouraged to understand the development and effectiveness of human resource management in Asia.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…This research examines the human resource management (HRM) methods in five Asian countries, highlighting their difficult nature and the desire to realize contextual elements very well. Future research must inspect unique determinants, conduct comparative research, and do longitudinal research to recognize the dynamic nature of human resource management (HRM) in Asia [9]. This study analyzes the migration styles of younger Europeans in Asia, highlighting their usage of motility to navigate unconventional migration routes.…”
Section: Introductionmentioning
confidence: 99%